ANALISIS PENGARUH SUBSTITUSI BAN BEKAS TERHADAP DURABILITAS DAN FLEXSIBILITAS ASPAL AC-WC - Rosyad, Farlin; Sakti, Redho Muhammad; Irham, Irham; Wahab, Wahyuni (Rang Teknik Journal, 2024)
The increase in tyre production has led to an increase in tyre rubber waste, which is harmful to the environment. The use of rubber tyres as a substitute additive material in concrete or laston (AC-WC) is one way out to reduce unused rubber tyre waste. The purpose of this research is to determine the effect of the use of used rubber tyres on the Durability and Flexibility values of the laston layer mixture (AC-WC) and to determine the optimum mixture component value for Durability and Flexibility in the laston layer mixture (AC-WC). This research uses experimental methods, namely, quantitative research methods. In this study, researchers used a percentage of used tyre mixture of 1%, 2%, 3% and 4% of the weight of the test specimen and 0% as a normal mixture. The results of this study indicate that the flow value in the standard marshall percentage of used tyre rubber 1% and 2% meets the 2018 revised Bina Marga Specification 2 between 2-4 mm. While the percentage of used tyre rubber 3% and 4% does not meet the 2018 revised Bina Marga Specification 2 between 2-4 mm. Because the greater the percentage of used tyre rubber, the greater the flow value obtained. In Marshall Stability, it can be concluded that the remaining Marshall Stability value of the normal AC-WC asphalt mixture is 90.67%, this value meets the Bina Marga 2018 Revision 2 Specifications with standard Specifications 90%.  Keywords: laston layer mix (AC-WC), durability, flexibility, waste rubber tire, marshall